SSL Complete Guide - HTTP to HTTPS - Stashchuk, Bogdan (Packt Publishing, 2019)
Configure NGINX and Apache, install free SSL/TLS certificates from Let's Encrypt, configure Cloudflare, and create CSR requests About This Video TLS certificate structure Cloudflare reverse proxy with free SSL certificates CSR (Certificate Signing Request), domain validation, and certificate installation In Detail This course is all about securing websites with SSL/TLS certificates. We start by exploring the basics of symmetric encryption algorithms such as AES, asymmetric encryption (RSA), and hashing protocols (MD5 and SHA). Also, we will explain the fundamentals of computer networks and TCP/IP stacks; for that, we use the Wireshark traffic analyzer. You will learn about the structure of SSL/TLS certificates. Also, you will understand why CAs (Certificate Authorities) are needed and how the chain of trust is built. We will perform multiple practice activities: Buy a domain and configure DNS settings Use the Certbot ACME client to automatically obtain a free SSL certificate from Let's Encrypt With the help of OpenSSL, generate RSA keys and self-signed certificates Secure WordPress with Apache using SSL/TLS certificates Create a CSR (Certificate Signing Request) via OpenSSL and submit it to the CA server Configure Cloudflare for your domain and set up different SSL operation modes Install and configure NGINX web servers for SSL/TLS certificates Migrate from HTTP to HTTPS Redirect all traffic using HTTP 301 redirect from HTTP to HTTPS No prior knowledge of computer networks, encryption, or configuring web servers is required. This course will teach you everything from scratch-from simple setups to complex solutions. If you want to master SSL and HTTPS in-depth, this course is for you!